Intensi Agripreneurship di Kalangan Mahasiswa Pertanian Indonesia - Sugiyarto, Sugiyarto; Windani, Isna (Universitas Islam Kadiri, 2025)
Agricultural development in Indonesia is facing not only on natural resources but also on human resources issue related to the lack of farmer regeneration. This study aimed to 1) understand the youth perception on agricultural sector, 2) identify the level of intention of the youth to agripreneurship, 3) analyze the determinant factors of the intention to agripreneurship. This study conducted online by asking 211 undergraduate students from several universities in Java and outer Java to fulfill online structured questionnaire. Descriptive analysis and structural equation model were employed in the research analysis. The results showed 1) the youth saw that agricultural sector was still interesting and had a good opportunity to develop their carrier in the future, 2) the intention of the youth to be an agripreneur was strong, and 3) the capital (financial and social capital) and perception to agricultural sector positively determined the intention to be agripreneur, meanwhile there were no statistical evidence that the social background of the youth determined the level of intention.